ANALISIS SISTEM E-FILING, E- SPT DAN E-FORM TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI SPT TAHUNAN KPP PRATAMA BATAM - ahue, ahue; Siregar, Dian Lestari (SCIENTIA JOURNAL, 2021)
Various reform efforts have been made by the Directorate General of Taxes in order to increase state revenue in the taxation sector, one of which is an online tax reporting system. The object of this research discusses the analysis of the E-Filing, E-Spt and E-Form systems on individual taxpayer compliance at KPP Pratama Batam Selatan. In this study, researchers used a population of 100 respondents. This study was analyzed using the SPSS system (Statistical Products and Service Solutions). The results showed that the e-Filing variable did not have a significant effect on individual taxpayer compliance. It is said to be insignificant because the significance value of the e-Filing variable is 0.257 which is greater than the α value of 0.05. The E-SPT variable has a positive and significant effect on Individual Taxpayer Compliance. It is said to be significant because the value of the E-SPT variable has a significant value of 0.004 where the value is smaller than the α value of 0.05. The E-Form variable has a positive and significant effect on Individual Taxpayer Compliance. It is said to be significant because the spss value of the E-Form variable is significant 0.003 smaller than the α value of 0.05.